Isolation of Staphylococcus aureus from Chicken Meat and the Chicken Slaughterhouse Environment at Traditional Markets in Kendari City - Yamin Yaddi; Fitrianingsih Fitrianingsih; Restu Libriani; La Ode Sahaba; Surahmanto Surahmanto; Achmad Selamet Aku; Fitria Dewi (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Bacterial contamination in chicken meat is an indicator in determining the quality of food ingredients. Contaminant bacteria cause damage to meat and cause foodborne disease due to their metabolite products. Staphylococcus aureus is a bacterium that causes food poisoning due to its toxin products. Meat contamination by Staphylococcus aureus occurs through the food itself or through the environment where it is processed. This study aims to isolate and identify the presence of Staphylococcus aureus in chicken meat and the production environment. The results of this study indicate that Staphylococcus aureus can be isolated from chicken meat (40%), the floor of the holding cage (26.67%), the place for bleeding (62.22%), the hair removal machine (64.44%) and the table. processing (80%) as a representation of environmental quality assessment indicators. These results illustrate that it is necessary to improve chicken slaughterhouses in traditional markets to increase and guarantee the quality of chicken meat.